Investigating People’s Perception towards the Homelessness - Noor Ashikin MOHD ROM; Rishetra VAMALATITHAN; Nurbani MD. HASSSAN (Communications of International Proceedings, 2021)
The number of homelessness keep increasing especially in big cities and this phenomenon is viewed as weaknesses of the whole system in handling such situation. This study proposes to investigate people’s perception on homeless people. The qualitative techniques will be employed in the study. The study on people’s perception towards the homelessness is significant to determine the design of the durable and practical policy.
Keywords: Homelessness; attitude; perception; policy.